GAMBARAN BAKTERIOLOGIS TANGAN PERAWAT - Zuhriyah, Lilik (Jurnal Kedokteran Brawijaya, 2004)
Hand hygiene of health-care workers become an important thing since hands of health-care personnel arethe most frequent vehicles for nosocomial ifections. However, adherence of hand washing has been poor. This study was to obtain bacteriological descriptions of nurses’s hand. The study was conducted in Surgical  and Medical Intensive Care Services using A Cross Sectional Survey. Populationwere all of nurses in ICU and CVC room. Purposive Sampling was carried to obtain samples of  20 nurses. Measurement was carried on January 2004. Bacteriological descriptions of nurses’s hand was measured by swabbing ofright side after hand washing. Examination by hand swab with positive result were found in 20% of nurses. Species of bacteria which were found from nurses’s hand were Staphilococcus epidermidis and Enterobacter aerogenes. It can be concluded that species of bacteria found from had swabbing are non pathogenic bacteria. Efforts to improve of all health workers for hand hygiene appropriate with procedures are still needed. Focusing on had washing practice among nurses and others health workers are needed for the following research. Keywords: bacteriological, nurses’s hand